IDEOLOGICAL AND LEGAL POLICY PERSPECTIVES ON THE EXISTENCE OF ROHINGYA REFUGEES IN INDONESIA - Fuady, Muhammad Irham; Zulkarnain, Zulkarnain; Berlian, Hangrengga (Journal Philosophy of Law, 2024)
The occurrence of the Rohingya and Rakhine ethnic conflict is a religious conflict in Myanmar between Islam and Buddhism that makes attention to the world, because the conflict resulted in ethnic Rohinya fleeing to neighboring countries, one of which is Indonesia. Indonesia is a legal state that upholds the sovereignty of the Unitary State of the Republic of Indonesia, but in addition to sovereignty there is a state ideology in the form of Pancasila which contains many humanitarian values. The purpose of this research is to find out the legal policies contained in Indonesia and how the Pancasila values are viewed towards foreigners who are refugees. The type of research used is normative or commonly called library research, the research approach is carried out with descriptive analysis with data collection techniques in the form of literature review, books, mass media, articles, journals, internet. The results of this study are that actually internationally normative, Indonesia has not ratified the 1951 convention and 1956 protocol, but Indonesia itself has specific guidelines for handling refugees contained in Presidential Regulation Number 125 of 2016 and Law Number 37 of 1999. There are several things that make Indonesia unable to ratify the Convention, namely if Indonesia ratifies it must comply with the convention, for example Article 17 of the 1951 Convention, namely the state must be responsible for providing jobs for refugees, even though Indonesia as a developing country still has a high unemployment rate, then Article 21 there is a provision that refugees must be given a house, even though the poverty rate of Indonesian citizens is still high and other articles that the Indonesian people have not been able to fulfill what is required in the convention. Then if seen from the point of view of Pancasila, Pancasila contains humanitarian values which means that upholding the human rights of anyone, including Rohingya refugees.